Pengembangan Sumber Belajar Geografi Berbasis Weblog Pada Pokok Bahasan Biosfer Di SMA - I kadek Budi Artawan; Daud Yusuf; Nurdin Mohamad (Universitas Negeri Gorontalo, 2023)
This study aims to determine the development of Weblog-based learning media on the subject matter of the biosphere. Weblog is an online-based application service that can be used to create learning media related to biosphere material. This research uses a development research method with the ADDIE model which was first developed by Raiser and Mollenda which was used as an approach in compiling learning media. Data collection techniques through observation, interviews, questionnaires and documentation. The instruments used are in the form of assessment criteria to determine the feasibility of media from material experts, media experts, and geography teachers as well as student responses to learning media using questionnaires. Data was collected in the form of research results on the quality of learning media and suggestions for product revision. The results of the material expert validation show that the media validation value given by validator 1 or material / content expert with valid category is 86.15%, validator II or product design expert gives a very valid assessment of 87.77%, then for validator III or in this case geography teacher subject experts give a very valid category assessment of 98%. The average response from students to this learning medium was 85.5%. Thus Weblog-based learning media on biosphere material can be used as a learning medium in schools and get a very good response by students.